MOTIF PENGGUNAAN SWAFOTO SEBAGAI BENTUK EKSISTENSI DIRI DALAM AKUN INSTAGRAM (STUDI DESKRIPTIF KUALITATIF PENGGUNAAN FOTO SWAFOTO DALAM MEDIA SOSIAL INSTAGRAM SEBAGAI BENTUK EKSISTENSI DIRI PADA MAHASISWA UNIVERSITAS 17 AGUSTUS 1945 SURABAYA) - Oktavia, Dwi Ajeng Rindayu; Sudaryanto, Edy (Universitas 17 Agustus 1945 Surabaya, 2018)
Selfie activity has now become a trend for people who like to upload photos to social media,especially Instagram, so it can be seen by the other users. Most of them do not upload their selfies tosocial media Instagram for no reasons, but they want to know about how many people are going togive attention or like and comment on their selfie. Hope to get some reward as likes and commentsfrom the other users make them always try so hard to make an interesting photo.Because of the phenomenon, the writer interested in conducting a research on the motive of usingphotos selfie as a form of existence in social media Instagram. This study use qualitative researchmethods, and use Motive Maslow Theory and also the uses and gratifications theory. For collect theresearch data, the writer do some interview and observations to the students of the University 17Agustus 1945 Surabaya as informants in this research. The results of this reasearch indicate that thereare some motive for the uses of photos selfie to show self-existence on Instagram, which is hoping toreceive social responses that can affect their existence, following what’s the trending so they not lookout of date, and that their existence is recognized by people around.Keywords: Motive, Selfie, Existence, Social Media